SUSPECTED PREDICTION USING CRIMINAL INVESTIGATION TRACKER (International Journal of Food and Nutritional Sciences, 2022)
Criminal investigation tracker system that tracks the investigation status of criminal cases with logs and also predicts primary suspects. It is proposed to help agencies like CBI, CID and other such bureau ’s to speed up investigation process and track status of multiple cases at a time. It keeps logs of a case which includes case summary, people involved, disputes, past criminal history of those involved, Items recovered on scene and other details. It realizes the type of case, allows admin to update the status of investigation, upload more images of crime, items found on scene etc. It allows authorized officers to check case status and look into its status online and also update any important info as and when needed. It also consists of a suspect prediction algorithm, Based on type of case, property, land, love or other entities involved the system studies past cases, it studies past criminal records of those involved and based on this data it provides suggestions of suspected persons in a logical order. It is designed to aid investigation teams to work collectively on cases, coordinate and also speed up the process by suggesting logical suspects based on data provided.